The Determinants of Prices in the FCC’s 700 MHz Spectrum Auction - Madden, Gary; Bohlin, E.; Kraipornsak, P.; Tran, Thien (Taylor & Francis, 2014)
This article examines the prices paid for 700 MHz licenses in recent Federal Communications Commission auctions. Econometric modelling confirms the presence of economies of scale and scope in wireless spectrum valuations. That is, higher prices are recorded for areas with large populations, whilst lower prices are realized for geographically large areas. Also, smaller geographic license areas appear to meet bidders’ demand more effectively, and licenses in areas with high incomes are sold at higher prices. Not surprisingly, more strict deployment requirements and the presence of harmful technical interference reduce prices. Also, paired spectrum receives higher prices than unpaired spectrum. Interestingly, high minimum opening bids and upfront deposits are associated with higher prices. Finally, competitive bidding places upward pressure on prices.